Left-wing butter vs. right-wing guns: Government ideology and disaggregated military expenditures - Łukasz Wiktor Olejnik (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This article demonstrates that the influence of government ideology on military expenditures is more nuanced than it was shown in previous research and using only aggregated military expenditures may provide ambiguous results. The disaggregation of military expenditures allows concluding that in the 29 studied EU and NATO countries, right-wing governments tend to spend more on military equipment and arms purchases, while left-wing governments tend to spend more on military personnel. Government ideology may also create compositional political budgetary cycles, due to the fact that left-wing governments fighting for re-election significantly increase personnel expenditures in election years, while right-wing governments spend significantly more on arms for soldiers. Moreover, using a newly created dataset of election results in 510 municipalities or constituencies with military bases in 29 EU and NATO countries allows concluding that governments with above-average support of military-related voters in previous elections spend more on the military during the entire term, which suggest that ruling politicians support their core voters.
Keywords: H56; H76; 330; economic theory of alliances; peace and defence economics; military burden